The impact of cultural tourism on local traditions - I Ketut Surata; I Made Sumartana; I Gusti Bagus Rai Utama (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research paper investigates the impact of cultural tourism on the preservation of local traditions in Penglipuran Village, Bali, aiming to understand how tourism influences community practices and identity. The study employs a qualitative case study methodology, utilizing in-depth interviews, participatory observation, and document analysis to gather comprehensive data from local residents, community leaders, and tourism stakeholders. Key findings reveal that while cultural tourism has generated economic benefits and increased awareness of local heritage, it has also led to significant alterations in traditional practices, including the commercialization of sacred ceremonies and changes in architectural styles. The research identifies both supporting factors, such as community engagement in tourism management, and hindering factors, such as the risk of cultural dilution. Notably, the study emphasizes the importance of community perspectives in shaping sustainable tourism strategies that balance economic growth with cultural preservation. The novelty of this research lies in its focused examination of a specific village context, highlighting the unique dynamics between cultural tourism and local traditions while providing actionable recommendations for enhancing community involvement in heritage preservation. This work contributes to the broader discourse on sustainable tourism by offering insights into effective practices that can be adopted by other communities facing similar challenges.